2017
DOI: 10.1007/s11886-017-0818-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Dyslipidemias to Prevent Cardiovascular Disease in Patients with Type 2 Diabetes

Abstract: Purpose of Review Current preventive and treatment guidelines for type 2 diabetes have failed to decrease the incidence of comorbidities, such as dyslipidemia and ultimately heart disease. The goal of this review is to describe the physiological and metabolic lipid alterations that develop in patients with type 2 diabetes mellitus. Questions addressed include the differences in lipid and lipoprotein metabolism that characterize the dyslipidemia of insulin resistance and type 2 diabetes mellitus. We also examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 122 publications
2
30
0
2
Order By: Relevance
“…Add-on ezetimibe and other nonstatin therapies have been prescribed to reduce the residual cardiovascular risk in diabetic patients. 14,15 The effect of the add-on ezetimibe to simvastatin treatment on the LDL cholesterol levels in HC (21% reduction) and DM (24% reduction) observed in this study was similar to the effect of the combined therapy using different types and regular dosages of statins in diabetic and nondiabetic hypercholesterolemics as well as subjects with coronary heart disease. [16][17][18][19][20] Interestingly, add-on ezetimibe also reduced the levels of triglycerides and VLDL cholesterol in DM patients, suggesting that ezetimibe contributes to better metabolic control in diabetics.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Add-on ezetimibe and other nonstatin therapies have been prescribed to reduce the residual cardiovascular risk in diabetic patients. 14,15 The effect of the add-on ezetimibe to simvastatin treatment on the LDL cholesterol levels in HC (21% reduction) and DM (24% reduction) observed in this study was similar to the effect of the combined therapy using different types and regular dosages of statins in diabetic and nondiabetic hypercholesterolemics as well as subjects with coronary heart disease. [16][17][18][19][20] Interestingly, add-on ezetimibe also reduced the levels of triglycerides and VLDL cholesterol in DM patients, suggesting that ezetimibe contributes to better metabolic control in diabetics.…”
Section: Resultssupporting
confidence: 73%
“…Statins are the first line of treatment for diabetic dyslipidemia that substantially reduces LDL cholesterol as well as the risk of CVD. Add‐on ezetimibe and other nonstatin therapies have been prescribed to reduce the residual cardiovascular risk in diabetic patients …”
Section: Discussionmentioning
confidence: 99%
“…The data on the effect of P. stratiotes aqueous extract on lipid profile is presented in Table 3.Studies have shown that dyslipidemia is a crucial feature of diabetes. [20][21][22] The key components of diabetic dyslipidemia include alterations on the plasma lipid profiles (LDLcholesterol, TG and lowered HDL-cholesterol), which were evidently observed in the present study ( Table 3). The TC, TG and LDLcholesterols of the untreated diabetic group were significantly (p<0.05) elevated while the HDL-cholesterol was significantly (p<0.05) lowered compared to the normal untreated group (Table 3).…”
Section: Resultssupporting
confidence: 64%
“…These receptors recognize conserved pathogens-associated molecular patterns (PAMPs), inducing innate immune responses which are essential for host defenses [14]. They can also be activated by endogenous molecules (damage-associated molecular patterns, DAMPs) released under conditions of cellular stress or tissue injury [15] as free fatty acids and glycation end products [16]. TLRs and nucleotide binding and oligomerization domain (NOD)-like receptors (NLRs) trigger the formation of an inflammasome in the cytoplasm, a multiprotein complex, when active, recruits inactive procaspase-1 molecules to form activated caspase-1 [17].…”
Section: Introductionmentioning
confidence: 99%